2009
DOI: 10.4161/hv.5.8.8571
|View full text |Cite
|
Sign up to set email alerts
|

Seropersistence of tick-borne encephalitis antibodies, safety and booster response to FSME-IMMUN®0.5 ml in adults aged 18-67 years

Abstract: A clinical study was carried out to evaluate the persistence of tick-borne encephalitis (TBE) antibodies 2 and 3 years after a primary vaccination series (three-dose regimen), and to assess the antibody response to a booster vaccination with FSME-IMMUN. Volunteers (N = 347, 18-67 years) who had received two doses of either FSME-IMMUN or Encepur adults and a third vaccination with FSME-IMMUN were enrolled. Seropositivity rates were assessed by ELISA and neutralization test (NT). After the primary series, seropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…20 ELISA values > 126 VIE U/mL obtained by the Immunozym ® ELISA were considered positive. 21 The Enzygnost ® ELISA categorized results > 10.32 U/mL as positive.…”
mentioning
confidence: 99%
“…20 ELISA values > 126 VIE U/mL obtained by the Immunozym ® ELISA were considered positive. 21 The Enzygnost ® ELISA categorized results > 10.32 U/mL as positive.…”
mentioning
confidence: 99%
“…A study on TBE booster vaccination reporting 6-year follow-up data showed that antibody levels were 2 times lower in vaccinees 60 years of age or older, implying some waning of antibodies with increasing age [28]. A study investigating the seropersistence of TBE antibodies in adults aged 18-67 years concluded that the comparatively low seropositivity rates in vaccinees above 50 before their first booster vaccination emphasized the importance of administering the first booster vaccination no later than 3 years after the completion of primary immunization [29].…”
Section: Tbe and The Ageing Immune Systemmentioning
confidence: 94%
“…More extensive clinical data are available for inactivated, whole-virus vaccines to prevent diseases caused by flaviviruses, which structurally resemble alphaviruses, such as tick-borne encephalitis virus (TBEV), Japanese encephalitis virus, and yellow fever virus (21)(22)(23). The most extensively studied flavivirus vaccine is an alumadjuvanted inactivated whole-virus TBEV vaccine, which has been demonstrated to be safe and immunogenic in a multitude of clinical studies (24)(25)(26)(27)(28)(29)(30) and which has been used in Europe for several decades. In field studies, it has been demonstrated that three immunizations with a 2.4-g dose of the inactivated wholevirus TBEV vaccine provide approximately 99% effectiveness in preventing tick-borne encephalitis (22).…”
Section: Discussionmentioning
confidence: 99%